Physiological and biomechanical responses to walking underwater on a non-motorised treadmill: effects of different exercise intensities and depths in middle-aged healthy women. - Benelli, Piero; Colasanti, Franca; Ditroilo, Massimiliano; Cuesta-Vargas, Antonio; Gatta, Giorgio; Giacomini, Francesco; Lucertini, Francesco (Taylor & Francis, 2014)
Non-motorised underwater treadmills are commonly used in fitness activities. However, no studies have examined physiological and biomechanical responses of walking on non-motorised treadmills at different intensities and depths. Fifteen middle-aged healthy women underwent two underwater walking tests at two different depths, immersed either up to the xiphoid process (deep water) or the iliac crest (shallow water), at 100, 110, 120, 130 step-per-minute (spm). Oxygen consumption (VO2), heart rate (HR), blood lactate concentration, perceived exertion and step length were determined. Compared to deep water, walking in shallow water exhibited, at all intensities, significantly higher VO2 (+13.5%, on average) and HR (+8.1%, on average) responses. Water depth did not influence lactate concentration, whereas perceived exertion was higher in shallow compared to deep water, solely at 120 (+40%) and 130 (+39.4%) spm. Average step length was reduced as the intensity increased (from 100 to 130 spm), irrespective of water depth. Expressed as a percentage of maximum, average VO2 and HR were: 64-76% of peak VO2 and 71-90% of maximum HR, respectively at both water depths. Accordingly, this form of exercise can be included in the "vigorous" range of exercise intensity, at any of the step frequencies used in this study.
https://openpolicyfinder.jisc.ac.uk/id/publication/5753
Keywords: Hidroterapia; Non-motorised underwater treadmill; Oxygen consumption; Heart rate; Blood lactate